Changes in floral bouquets from compound‐specific responses to increasing temperatures - Gerard Farré‐Armengol; Iolanda Filella; Joan Llusià; Ülo Niinemets; Josep Peñuelas (Global Change Biology, 2014)
We addressed the potential effects of changes in ambient temperature on the profiles of volatile emissions from flowers and tested whether warming could induce significant quantitative and qualitative changes in floral emissions, which would potentially interfere with plant–pollinator chemical communication. We measured the temperature responses of floral emissions of various common species of Mediterranean plants using dynamic headspace sampling and used GC ‐ MS to identify and quantify the emitted terpenes. Floral emissions increased with temperature to an optimum and thereafter decreased. The responses to temperature modeled here predicted increases in the rates of floral terpene emission of 0.03–1.4‐fold, depending on the species, in response to an increase of 1 °C in the mean global ambient temperature. Under the warmest projections that predict a maximum increase of 5 °C in the mean temperature of Mediterranean climates in the Northern Hemisphere by the end of the century, our models predicted increases in the rates of floral terpene emissions of 0.34–9.1‐fold, depending on the species. The species with the lowest emission rates had the highest relative increases in floral terpene emissions with temperature increases of 1–5 °C. The response of floral emissions to temperature differed among species and among different compounds within the species. Warming not only increased the rates of total emissions, but also changed the ratios among compounds that constituted the floral scents, i.e. increased the signal for pollinators, but also importantly altered the signal fidelity and probability of identification by pollinators, especially for specialists with a strong reliance on species‐specific floral blends.